KEMAMPUAN PENALARAN ADAPTIF SISWA DENGAN PENDEKATAN PROBLEM BASED LEARNING DALAM MATERI HIMPUNAN DI SMP - Isda Nursida; Edy Yusmin; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe fact in math education is adaptive reasoning ability that is still low. Students’ adaptive reasoning ability are influenced by some factors, one of them is teacher as a center of learning so that the mathematical concepts are conveyed in an informative manner without deep understanding. Therefore, Problem Based Learning (PBL) approach is used to increase adaptive reasoning ability. This research aimed to explore information about students’ adaptive reasoning ability in set theory subject matter of grade VII at SMPN 7 Sungai Raya. The method of this research is experiment and research design is one-shot case study. The samples of this research are 27 students of grade VII D at SMPN 7 Sungai Raya. Essay questions are used to collecting the students’ adaptive reasoning ability outcomes. The results of data analysis showed that the average of posttest score is 73,61. Based on the t-test with the significance level α=5% found that the adaptive reasoning ability of students after learning with the Problem Based Learning (PBL) approach is included in the high category. It means that application of  Problem Based Learning (PBL) approach is good in set theory subject matter at grade VII SMPN 7 Sungai Raya. Keywords: Adaptive Reasoning Ability, Problem Based Learning Approach